Assessing the Design Preferences of Ageing Residents in Malaysian Elderly Care Homes - Alice Sabrina Ismail , Roshida Abdul Majid , Fadhlina Ahmad Taufik , Norshahida Azili , Muhammad Nor Haziq Zamry (International Journal of Advanced Science and Technology, 2020)
Many of the existing elderly care homes in Malaysia are lacking in terms of designconsideration to fulfil the requirements of seniors as they age further. Past literature onelderly care homes nevertheless, only much focuses on the aspect of management andservices, social health care program and facilities as well as living arrangementssuitability for the elderly residing in the elderly care homes. None, however, attempts ondiscussing and determining the best practice guidance in terms of design preferences tofulfill ageing resident’s needs. This paper discusses on the design issues and challenges incurrent elderly care homes followed by examination through the appearance andconfiguration of both the exterior and interior of the existing home care. This is vital toestablish appropriate design strategies in terms of architectural design layout involvingthe quality of home environment in terms of living, emotional and facilities comfortwhereas maintaining the existing cultural values. This study adopts mixed methodologystrategy framed by the interpretivism paradigm approach in which all qualitative datawere analyzed using hermeneutics and coding whilst the quantitative data were examinedusing SPSS technique. Findings indicate that ageing residents much prefer home designwith proper contextual responsiveness, appropriate building envelope, suitable siteplanning with comfortable unit dwellings space as well as suitable form making qualities.This paper is of benefit for future designers, builders, developers and related authoritiesto improve the design quality of elderly housing in Malaysia in the aspect of physicalplanning guidelines.